Disulfiram oxy-derivatives induce entosis or paraptosis-like death in breast cancer MCF-7 cells depending on the duration of treatment - Solovieva, Marina; Shatalin, Yuri; Odinokova, Irina; Krestinina, Olga; Baburina, Yulia; Mishukov, Artem; Lomovskaya, Yana; Pavlik, Liubov; Mikheeva, Irina; Holmuhamedov, Ekhson; Akatov, Vladimir (Biochimica et biophysica acta. General subjects, 2022)
Dithiocarbamates and derivatives (including disulfiram, DSF) are currently investigated as antineoplastic agents. We have revealed earlier the ability of hydroxocobalamin (vitamin В12b) combined with diethyldithiocarbamate (DDC) to catalyze the formation of highly cytotoxic oxidized derivatives of DSF (DSFoxy, sulfones and sulfoxides). Electron and fluorescent confocal microscopy, molecular biology and conventional biochemical techniques were used to study the morphological and functional responses of MCF-7 human breast cancer cells to treatment with DDC and B12b alone or in combination. DDC induces unfolded protein response in MCF-7 cells. The combined use of DDC and B12b causes MCF-7 cell death. Electron microscopy revealed the separation of ER and nuclear membranes, leading to the formation of both cytoplasmic and perinuclear vacuoles, with many fibers inside. The process of vacuolization coincided with the appearance of ER stress markers, a marked damage to mitochondria, a significant inhibition of 20S proteasome, and actin depolimerization at later stages. Specific inhibitors of apoptosis, necroptosis, autophagy, and ferroptosis did not prevent cell death. A short- time (6-h) exposure to DSFoxy caused a significant increase in the number of entotic cells. These observations indicate that MCF-7 cells treated with a mixture of DDC and B12b die by the mechanism of paraptosis. A short- time exposure to DSFoxy caused, along with paraptosis, a significant activation of the entosis and its final stage, lysosomal cell death. The results obtained open up opportunities for the development of new approaches to induce non-apoptotic death of cancer cells by dithiocarbamates. [Display omitted] •Diethyldithiocarbamate (DDC) induces unfolded protein response in MCF-7 cancer cells.•Products of vitamin B12b-catalyzed DDC oxidation induce nonapoptotic MCF-7 cell death.•Products of DDC oxidation (DSFoxy) induces severe damage of ER, nuclei and mitochondria.•Short-time exposure to DDC + B12b leads to induction of entosis and paraptosis.•Prolonged treatment with DDC + B12b leads to paraptosis-like MCF-7 cell death.